Protest and the rise of left-nationalist challengers: evidence from Germany - Schürmann, Lennart; Borbáth, Endre; Hutter, Swen (Social movement studies, 2025)
The cost-of-living crisis, unfolding in the shadow of Russia's invasion of Ukraine, highlighted policy positions not traditionally represented in European party systems and protest politics. Our study asks why large-scale protests, widely anticipated during Germany's 'Hot Autumn' of 2022, did not materialize despite a severe cost-of-living crisis. Drawing on insights from social movement studies, we test the long-standing argument that successful mobilization depends on the presence of mobilizing agents that align programmatically with existing demand. We use an innovative multi-method design that combines individual-level survey data with protest event analysis to examine both protest potential and actual mobilization. The survey includes a conjoint experiment to identify factors influencing protest potential. Our findings show that despite strong public sympathy, the 'Hot Autumn' saw only moderate protest participation, as established trade unions and political parties from both the left and the right struggled to capitalize on the momentum. Instead, the left-nationalist B & uuml;ndnis Sahra Wagenknecht (BSW) emerged as a new challenger, offering an economically left-wing, culturally nationalist platform that resonated with protest sympathizers. By analyzing how ideological (mis)alignment shapes protest dynamics, our study contributes to research on party-movement interactions and demonstrates how the two-dimensional structure of political conflict increasingly challenges traditional left-wing actors' ability to mobilize.
Gesehen am 03.12.2025